Strategy of National and Economic Security - D. M. Zhuravlev; V. K. Chaadaev (Управленческое консультирование)
The recent events related to the crisis of political power in a number of states in the post-Soviet space and the desire of their governments to destroy the established economic ties with the Russian Federation lead to local sectoral crises, inflation and a slowdown in the growth of gross national product. Objective requirements for changing economic processes in the direction of stabilizing the socio-political situation dictate to the leaders of various levels (federal, regional, municipal and commercial), among the strategic tasks, the need to develop and apply an effective set of tools and methods for managing socio-economic systems in all phases and stages of functioning of the national economic complex. The solution of such problems, first of all, involves the formalization and specification of factors related to the economy that can have a negative impact on critical infrastructure, sectors of the economy and processes that are vital for the sustainable functioning of the state. The foregoing determined the purpose of the study — to analyze the concept of national security and build a conceptual structure of risk vectors that have a significant impact on the critical infrastructure necessary for the formation of a country's accelerated development strategy (search and justification of points and poles of national economic growth). In the process of work, the most important processes, from the standpoint of national and economic security, have been formalized that ensure comfortable and safe living conditions for citizens on the territory of the country; the essence of the main, from the point of view of the authors, external and internal risk factors that directly affect both the growth of the economy and the stabilization of relations in society is considered. In order to minimize negative factors, it is proposed to develop a long-term strategy for the rapid development of the national economy with a clear formalization of specific final goals (measurable and achievable) using, as a tool for developing an effective system of interactions, digital twins of control objects. As a methodological basis, it is proposed to use the strategizing methodology of academician V.L. Kvint.